Efficacy of Bacillus clausii UBBC - 07 spores in the amelioration of oral mucositis in head and neck cancer patients undergoing radiation therapy - Mehdi Ali Mirza; D Aruna; Monica Irukulla (Cancer Treatment and Research Communications, 2022)
Background: : The natural flora of healthy mucosa offer protection to the host. The loss of this barrier during radiotherapy enhances insults from physical, chemical and microbial agents. Methodology: : A randomized, double blind, placebo-controlled, parallel study on forty-six patients who underwent radiotherapy for head and neck cancers was undertaken. Patients were randomized either to standard treatment plus Bacillus clausii UBBC07 or standard treatment plus placebo. Bacillus clausii UBBC07 was given as an oral suspension of 2 billion spores twice every day for 30 days or until completion of total fractions of radiation. Grading of the mucositis was performed using CTCAE v.4.03 severity scale. The time taken for the appearance, resolution and severity of mucositis was evaluated. Results: : There was a significant increase (p < 0.01) in median time for the onset of mucositis i.e., 10 days in test and 8 days in control groups respectively. The median time for remission was found to be 12 days in test and 14 days in the control group (p < 0.05). Grade IV mucositis was observed in no patients in test group and 2 patients in the control group (p < 0.05). No adverse events attributed to the Bacillus clausii were seen. Bacillus clausii UBBC07 therapy delayed the onset, decreased the time to remission and displayed strong impact on suppressing the occurrence of high-grade mucositis amongst the test group. Conclusions: : This study provides a positive trend that probiotics like Bacillus clausii UBBC07 spores could act as a tool to ameliorate oral mucositis.